Analisis Perbandingan Efisiensi, Kualitas Aset, Dan Stabilitas Bank Umum Konvensional Dan Bank Umum Syariah Yang Melakukan Pemisahan (Spin-Off) Di Indonesia Periode Tahun 2013-2017 - Uswatun Hasanah; Vanica Serly (Universitas Negeri Padang, 2019)
This research aims to compare the efficiency, asset quality, and stability of Islamic banks that do spin-off and conventional banks in Indonesia from 2013 until 2017. The variables used are overhead cost and cost income ratio as efficiency proxy, the loan loss reserves is a proxy of asset quality, and return on asset and equity to asset ratio are proxy of stability. The sampling technique is total sampling. The population in this study amounted to 22 banks. The statistics test used are descriptive statistic, Mann Whitney test, and Independent Sample t-Test. The results showed that there were no significant differences in efficiency and asset quality, but stability was significant difference from 2013-2017.